Acute and long-term success of left atrial anterior line and mitral isthmus line ablation in patients after mitral valve surgery. (3rd October 2022) - Lemes, C; Rottner, L; Heeger, C H; Maurer, T; Reissmann, B; Ouyang, F; Mathew, S; Metzner, A; Schlueter, M; Kuck, K H
Abstract: Background: Perimitral flutter and atrial fibrillation may occur in patients with prior surgical mitral valve (MV) repair or replacement and can be challenging for percutaneous catheter ablation. Objective: This study sought to determine the feasibility, acute success and durability of catheter ablation of atrial fibrillation or atrial tachycardia by way of a mitral isthmus line (MIL) or an anterior line (AL). Methods: A total of 81 patients (49 males, mean age 62±11 years) with prior MV replacement (n=30) or repair (n=51) underwent creation of a MIL (n=34) and/or an AL (n=72). Control group patients without prior surgery were matched 1:1 with the valve group (MIL, n=34; AL, n=72). Results: Acute bidirectional block of the MIL was successfully achieved in 24/34 cases and of the AL in 64/72 patients with prior MV surgery. In the control group, acute bidirectional block was achieved in 31/34 MIL patients and 65/72 AL patients. In terms of durability, the MIL valve subgroup showed the poorest results (probability of long-term failure 2.224, as opposed to 0.605 in the MIL control subgroup; hazard ratio [HR]=0.27, 95% confidence interval [CI], 0.11–0.65; p=0.004). In the AL subgroups, long-term outcomes were similar (probability of failure in AL valve subgroup 0.844 vs. AL control subgroup 1.03; HR=1.22, 95% CI, 0.66–2.26; p=0.523). Conclusions: Percutaneous creation of MIL and AL is feasible and safe in patients with prior MV replacement/repair. Because of poor long-term outcomes, MIL creation appears not advisable in patient with prior MV surgery. Funding Acknowledgement: Type of funding sources: None.